Nitrate Relationships between Stream Baseflow, Well Water, and Land Use in the Tomorrow-Waupaca Watershed - Henry Lin; Rebecca Cook; Byron Shaw (The Scientific World Journal)
We examined the use of stream baseflow water quality as a representative measure of mean ground water quality in the Tomorrow-Waupaca Watershed in central Wisconsin and the relationship between agricultural land use and watershed water quality. From 1997 to 1999, 38 stream sites were sampled for nitrate during winter and summer baseflow conditions. Some sites have been sampled during winter baseflow conditions since 1994. The land area contributing ground water to each stream sampling site was delineated, resulting in 38 sub-basins. In addition, over 3500 test results from private wells in the watershed were compiled and mapped using a Geographic Information System (GIS). Nitrate concentrations in stream baseflow and well waters were found to have strong positive correlation in the sub-basins of second order or higher. This indicates that stream baseflow may be valid for monitoring mean ground water quality in watersheds predominantly fed by ground water, where much of the stream nitrate is believed to originate from ground water. Analysis of seasonal variation in the stream data showed that winter nitrate concentrations were higher than summer concentrations, implying that winter stream monitoring may be more critical for the assessment of overall ground water quality in the watershed. We also found that, as the amount of agricultural land increased in each sub-basin, average nitrate concentrations in the well and stream waters also increased, suggesting a connection between agricultural land use and nitrate contamination of water resources in the watershed.